Подарок: роман / Джоанна Линдсей ; [перевод с английского Т. А. Перцевой] - Линдсей Джоанна (Шарм, 2002)
Экземпляры: ф.7 (2004) / Инвентарный номер: 48350 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Л 59 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44